Pathological Changes and Diagnostic Approaches of Johne’s Disease in Ruminants: A Review - Jaheed, Ezatullah (Journal of Natural Sciences – Kabul University, 2025)
Johne's disease (paratuberculosis) is a chronic enteric infection affecting domestic and wild ruminants caused by Mycobacterium avium subspecies paratuberculosis (MAP). Clinically, it manifests with chronic diarrhea, severe weight loss, and decreased productivity. Transmission occurs via the ingestion of contaminated feed, water, or milk, with MAP capable of persisting in the environment for long periods. This review aims to provide a comprehensive overview of the pathological alterations and diagnostic methodologies of Johne's disease, enhancing veterinary diagnostic capabilities and emphasizing its economic significance in livestock management. Findings indicate extensive and persistent intestinal lesions in affected animals. Despite the high costs, current diagnostic tests show limited sensitivity and no effective treatment exists. Effective control strategies remain undefined and require further development.